Pemanfaatan dana desa dalam meningkatkan pelayanan publik di Desa Pulerejo Kecamatan Ngantru - Nisa Budi Wijayanti; Bintis Ti'anatud diniati; Anisa Putri Puji Rahayu; Nur Atika; Salsabila Usulil Khikmah (LPPM ITB AAS Indonesia Surakarta, 2026)
This study examines the utilization of Village Funds in improving public service quality in Pulerejo Village, Ngantru District, Tulungagung Regency. The research is grounded in the importance of regional autonomy and the need for adequate funding to support rural infrastructure and essential public services. The objektive is to describe the planning, implementation, and challenges related to the management of Village Funds. A descriptive qualitative method was applied through field observations, in-depth interviews, and document analysis. The results indicate that the use of Village Funds in Pulerejo Village has been carried out in a participatory, transparent, and accountable manner through Village Deliberation forums, financial disclosure, and active supervision by the Village Consultative Body. The funds are utilized for infrastructure development, improvement of public service facilities, capacity building of village officials, and local economic empowerment. Challenges mainly arise from low digital literacy among some residents, which hinders the optimal implementation of electronic-based services. Overall, public service quality in Pulerejo Village is categorized as fairly good, with further potential for improvement through digital innovation and enhanced service facilities. Keyword: Utilization of Village Funds, Public Services, Village development.